Pseudolaric Acid B-Induced Autophagy Contributes to Senescence via Enhancement of ROS Generation and Mitochondrial Dysfunction in Murine Fibrosarcoma L929 Cells - Min Qi; Simiao Fan; Guodong Yao; Zhao Li; Haiyan Zhou; Shin-ichi Tashiro; Satoshi Onodera; Mingyu Xia; Takashi Ikejima (Elsevier, 2013)
Pseudolaric acid B (PAB) is the primary biologically active compound isolated from the root bark of P. kaempferi Gordon. Our previous study demonstrated that PAB induced mitotic catastrophe in L929 cells and indicated that only a small percentage (12%) of the cells undergoing mitotic catastrophe displayed an apoptotic phenotype after PAB treatment for 72 h. In this study, we found that a minority of the cells undergoing mitotic catastrophe ended in apoptosis, and a majority of them entered a period of senescence. Further data confirmed that PAB induced autophagy, reactive oxygen species (ROS) generation, and mitochondrial dysfunction in L929 cells. Subsequently, we found that autophagy inhibitors significantly delayed the senescence process, indicating that autophagy facilitated senescence. Moreover, ROS scavenger significantly decreased the autophagic level and improved mitochondrial function. Additionally, autophagy inhibitors effectively reduced ROS levels and ameliorated mitochondrial function. In conclusion, autophagy promoted senescence via enhancement of ROS generation and mitochondrial dysfunction in PAB-treated L929 cells. Keywords:: pseudolaric acid B, senescence, autophagy, reactive oxygen species (ROS), mitochondrial dysfunction